Tradisi Pernikahan Malam Songolikur Perspektif Hukum Islam: Studi Analisis Pendapat Kepala KUA Se-Kabupaten Jombang - Muhammad Hasan (IAI Nasional Laa Roiba Bogor, 2024)
Based on the author's observations during a practicum at the KUA, Tembelang District, Jombang Regency, the songolikur night wedding tradition was very troublesome for some of the headmen in several sub-districts in the District. Jombang because on that day dozens of marriages were held per sub-district and some even abandoned one of the pillars of Islam. On the one hand, the head of the KUA is subject to applicable customs, on the other hand the KUA does not dare to punish customs like this because customs like this on the other hand are against Islamic law itself. This is a type of field research. This time the author uses a qualitative method with a normative textual approach. The primary and secondary data were analyzed using Islamic legal theory. Songolikur night marriages, according to the views of the head of the KUA throughout Jombang Regency, are of the view that this marriage has two opinions, namely agreeing and disagreeing with its validity based on the dangers and benefits that occur in society, because there is no government agency that states with certainty regarding songolikur night marriages. For relevant government agencies, they should strengthen the rules regarding songolikur night marriages, so that there is no dualism between different laws.